Establishing sustainable learning venues : a guideline for training companies on the road to becoming more sustainable - Feichtenbeiner, Rolf [Verfasser]; Weber, Heiko [Verfasser]; Hantsch, Robert [Verfasser]; Berger, Nadja [Verfasser] (Bundesinstitut für Berufsbildung, 2022)
"Sustainability is one of the greatest social challenges in this day and age. Climate protection, fair working conditions and responsible neighbourhoods are becoming increasingly important issues for companies. A sustainable in-company learning environment helps employees to develop sustainability-related skills. These skills play a crucial role when it comes to acting in line with the guiding principle of sustainability. Companies are already doing a great deal to increase sustainability. However, there is still substantial potential to do more. This guideline describes four key areas for designing sustainable learning venues with a total of 13 areas of action. It provides practice-oriented suggestions for implementation in companies. The guideline thus not only brings fresh momentum for reporting, but also contributes to anchoring sustainable development more firmly into the structure of initial and continuing vocational education and training at companies." (Authors' abstract, BIBB-Doku)
Keywords: G 2.5 Nachhaltigkeit; S 3.2 Unternehmen und Behörden; 370; Berufsbildung; Nachhaltige Entwicklung; Betrieb; Lernort Betrieb; Kompetenzentwicklung